Univalent and Starlike Properties for Generalized Struve Function - Aaisha Farzana Habibullah; Adolf Stephen Bhaskaran; Jeyaraman Muthusamy Palani (International Journal of Mathematics and Mathematical Sciences)
We derive conditions on the parameters p, b, and c so that the function zwp,b,c(z), where wp,b,c(z) is the normalized form of generalized Struve function, belongs to the class S1⁎(α). Also, some sufficient conditions for the function zwp,b,c(z), to be in the class U(λ), are obtained.